Pengaruh Metode Pembelajaran Edutainment Terhadap Hasil Belajar Sub Tema Tugasku Sehari-Hari Disekolah Pada Siswa Kelas II SD Negeri 095194 Negeri Bayu - Ica Desria Sinurat (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence of edutainment learning methods on the learning outcomes of the sub-theme of my daily tasks at school for class II students at SDN 095194 Negeri Bayu for the 2023/2024 academic year. The type of research used in this research is quantitative research, which states that Quantitative research is research that takes the form of numbers and analyzes using statistics. The research design that will be used is experimental, in the form of a pre-experimental design that uses the